Ubiquitin-specific protease 1 acts as an oncogene and promotes lenvatinib efficacy in hepatocellular carcinoma by stabilizing c-kit - Zhangbin Chen; Yifei Ma; Zhitang Guo; Dingyuan Song; Zili Chen; Min Sun (Annals of Hepatology, 2022)
Introduction and Objectives: Ubiquitin-specific proteases (USPs) act as proto-oncogenes or tumor suppressors in a wide variety of cancers. In this study, we intended to explore the role of USP1 in hepatocellular carcinoma (HCC). Materials and Methods: The clinical significance of USP1 in HCC was analyzed based on The Cancer Genome Atlas (TCGA) data and immunohistochemical staining. siRNAs and lentivirus were used to knock down and overexpress indicated genes, respectively. qRT-PCR and immunoblotting were performed to examine mRNA and protein expression, respectively. CCK8, colony formation and PI/Annexin V-APC staining were performed to examine cellular function. Immunoprecipitation, coomassie blue staining, mass spectrum and immunoblotting were conducted to evaluate the interaction between USP1 and c-kit. Results: USP1 was over-expressed in HCC patients. Patients with high expression of USP1 had shorter overall and disease free survival than those with low expression of USP1. Functional results showed that USP1 was critical for HCC cell growth and proliferation. Immunoprecipitation and immunoblotting results suggested that USP1 interacted with c-kit and promoted the stability of c-kit, which is an important target of lenvatinib in HCC. Knockdown of c-kit reversed the oncogenic function of USP1 on HCC cell growth. Lastly, USP1 upregulation conferred higher sensitivity of HCC cells to lenvatinib treatment. Conclusions: Our study demonstrated that USP1 acted as an oncogene in HCC. It also promoted lenvatinib efficacy by stabilizing c-kit.